Analysis of Wastewater Quality of Jetis Batik, Sidoarjo - Tjahjani, Ida Kusnawati; Febrianti, Aulia Nur; Pramana, Yanatra Budi; Titisari, Manik Ayu (Jurnal Serambi Engineering, 2025)
Jetis Batik Industry in Sidoarjo is recognized as a prominent batik center in East Java.  Batik is known as an industry that uses both natural and synthetic dyes.  This can serve as a source of environmental pollution.  This study is to evaluate the quality of wastewater generated by Jetis Batik in Sidoarjo.  The determined quality is then evaluated according to Permenkes 02 of 2023 and PerGub Jatim Number 72 of 2013.  In this research, batik wastewater samples from 20 batik cottage industries in the Jetis region of Sidoarjo were used.  It is acknowledged that it does not meet the clean water quality standards set by the Minister of Health Regulation Number 02 of 2023 in terms of TDS parameters, turbidity, color, Fe, Mn, nitrate, nitrite, pH, and chromium.  Subsequent research in accordance with East Java Governor Law No. 72 of 2013 showed that TDS, pH, Fe, Mn, Cr, COD and BOD exceeded the quality criteria established by law.  In addition, according to the East Java Governor Regulation No. 72 of 2023, batik liquid waste is classified into categories I, II, III, IV, and seawater, which is considered unsuitable for discharge into the marine environment.  Immediate disposal of batik liquid waste into water sources without prior treatment poses a significant risk of environmental contamination.